THE EFFECT OF ANIMATED VIDEO MEDIA ON PREVENTION OF DENGUE HEMORRHAGIC FEVER (DHF) ON STUDENTS' KNOWLEDGE AND ATTITUDES AT SDN 002 SUNGAI PINANG - Alphard, Zada Alyfa; Chifdillah, Nino Adib; Bernadetha, Bernadetha (Jurnal Ayurveda Medistra, 2025)
In elementary school children, the selection of unqualified snacks is a problem that is a major concern in society. The animated video is made with a fun, simple storyline so that it can attract children's attention and the message conveyed can be maximized. Video animation is expected to change the mindset of children in preventing dengue hemorrhagic fever. This study aims to analyze the effect of animated video media on the prevention of dengue hemorrhagic fever on increasing knowledge, and attitudes of students of SDN 002 Sungai Pinang. This study used the Quasy experimental design research method with Time Series design. The population in the study was 5th grade students with amount of 45 people and used total sampling technique in sampling. There was an increase in the average knowledge score from 57.85 to 94.59. The average attitude score also increased from 60.52 to 93.11. Likewise with the average score of behavior, which increased from 62.22 to 94.17. Statistically, the results of the Wilcoxon test on the knowledge variable was ρ=0.000 < α 0.05 , and attitude ρ =0.000 < α 0.05. There is an influence of animated video media on increasing knowledge, and attitude in students of SDN 002 Sungai Pinang.